2017
DOI: 10.21595/jve.2017.18250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vibration in the treatment of children with spastic diplegic cerebral palsy

Abstract: Cerebral palsy is one of the leading causes of movement and posture disorders. Recently, Vibration, as a treatment method in clinical practice has been used as a complementary approach. The aim of this intervention was to determine the effect of vibration in addition to conventional therapy on spasticity, range of motion and gross motor functions in children with cerebral palsy. A total of 20 children with spastic diplegic cerebral palsy (7-10 years old) were randomly divided into two equal groups (conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…It reveals that there was no significant difference for balance between Group A and Group B were found. El-Shamy SM, [25], Dudoniene V. et al [26], Saquetto M. et al [27] were found that there were significant effect of vibration therapy on balance in the study.…”
Section: Role Of Segmental Vibration and Pelvic Stabilization Exercis...mentioning
confidence: 77%
See 1 more Smart Citation
“…It reveals that there was no significant difference for balance between Group A and Group B were found. El-Shamy SM, [25], Dudoniene V. et al [26], Saquetto M. et al [27] were found that there were significant effect of vibration therapy on balance in the study.…”
Section: Role Of Segmental Vibration and Pelvic Stabilization Exercis...mentioning
confidence: 77%
“…(p value ≥ 0.05). Katusic A. et al [18] Dudoniene V. et al [26], Jung Y. et al [28] concluded that vibration stimuli are significantly improves Gross motor performance in children with Cerebral Palsy.…”
Section: Role Of Segmental Vibration and Pelvic Stabilization Exercis...mentioning
confidence: 99%
“…For different reasons, 43 full-text papers were read in depth for eligibility, and 30 articles were removed. Finally, this meta-analysis comprised 13 papers [10,11,[23][24][25][26][27][28][29][30][31][32][33].…”
Section: Search Resultsmentioning
confidence: 99%
“…Table 1 lists the general characteristics of the subjects included in this study. Seventeen studies were finally included, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and coding was completed in the order of the group, number of subjects, gender, age, the gross motor function classification system (GMFCS) stage, and CP type.…”
Section: General Characteristics Of Included Studiesmentioning
confidence: 99%
“…[3] WBV has been effective in patients with cerebral palsy, as documented over the past 20 years. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] However, the outcomes are inconsistent and tend to depend on the experience and judgment of the subject using interventional devices in clinical practice. [4] because different application intensities were used in individual studies conducted on cerebral palsy patients.…”
Section: Introductionmentioning
confidence: 99%